Structural validity and reliability of the Spanish version of the White Bear Suppression Inventory (WBSI) in a sample of the general Spanish population - González Rodríguez, Manuel; Avero Delgado, Pedro; Rovella, Anna Teresa; Cubas León, Rosario (The Spanish Journal of Psychology, 2008)
This paper introduces the validation of the Spanish adaptation of the White Bear Suppression Inventory (WBSI) by Wegner and Zanakos (1994). A sample of 833 people from the general population completed the WBSI along with other questionnaires. The exploratory factor analysis and the confirmatory factor analysis supported a two-factor solution accounting for 51.8% of the cumulative variance. This structure is comprised of the two following factors: unwanted intrusive thoughts (= .87, r = .70) and actions of distraction and suppression of thoughts (= .80, r = .60). Both internal consistency reliability (= .89) and test-retest reliability (r = .71) showed adequate homogeneity, sound consistency, and stability over time. The results are discussed bearing in mind both isolated factors and the possible relationships of the suppression factor with automatic negative thoughts and insomnia.